(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
تتمثل إشكالية البحث بالمأزق التنموي الذي يتموضع فيه المجتمع العربي المعاصر, مقابل ذلك, سيتم التحليل على فرضية أن هذا المأزق, إنما يعود لسيطرة وعي أيديولوجي زائف للخروج من هذا المأزق, يكون بتوجه الفلسفة إلى المشكلة الاجتماعية بثلاث مسارات. المسار الأول: نقد الخطاب الثقافي العربي المعاصر. المسار الثاني: تشخيص الواقع الاجتماعي من خلال تحليل ثلاث مشكلات اجتماعية هي: (هجرة الأدمغة العربية, النظام التعليمي المترهل, تخلف الأنظمة والقوانين واستشراء الفساد). المسار الثالث: مساءلة التغير الثقافي والاقتصادي. The problem of this research focuses on the development crisis in contemporary Arab society. Analyzing this problem presupposes that this crisis is due to the false ideological conscious prevailing that society. However passing this crisis could be achieved through directing the philosophical grounds of the Arab social problems into three tracts: First, criticizing the modern Arab cultural product. Second, examining the Arab social reality through three different social problems: (1) Brain drain, (2) Inefficiency of the education system, (3) The underdeveloped systems of lows and rampant corruption.